Prevalence of Spondyloarthritis Among Patients Who Underwent Lumbar Disc Herniation Surgery - Özgül SOYSAL GÜNDÜZ,; Servet AKAR,; Dilek SOLMAZ,; Gerçek CAN,; Fatoş ÖNEN,; Nurullah AKKOÇ, (Archives of Rheumatology, 2020)
Objectives: This study aims to estimate the prevalence of spondyloarthritis (SpA) among patients who had been surgically treated for lumbar disc herniation (LDH), according to the modified New York (mNY) criteria for the diagnosis of ankylosing spondylitis and Amor, the European Spondyloarthropathy Study Group (ESSG), the Assessment of Spondyloarthritis International Society (ASAS) classification criteria for SpA. Patients and methods: The study included 321 patients (142 males, 179 females; mean age 49±10.8 years; range, 18 to 79 years) who underwent LDH surgery between April 2008 and May 2012 in the neurosurgery clinic of our hospital. Patients were contacted by phone on at least two attempts. Totally, 123 patients accepted to come to the outpatient clinic, while the remaining 198 agreed to be interviewed on the phone. Patients who agreed to come to the outpatient rheumatology clinic underwent clinical examination, and pelvic X-ray and magnetic resonance imaging (MRI) scan of the sacroiliac joints when indicated. Results: Inflammatory back pain was diagnosed in 108 patients (34%) and 40 patients (13%) according to Calin criteria and the ASAS criteria, respectively. Prevalence of SpA among all patients was estimated as 17.7% according to the ESSG criteria, and 8.7% according to Amor criteria. Five of the 308 pelvic radiographs had definite radiographic sacroiliitis as required by the mNY criteria. Four patients had a characteristic pattern of bone marrow edema on MRI examination in accordance with the ASAS definitions. The overall prevalence of sacroiliitis (MRI sacroiliitis+X-ray sacroiliitis) among the patients who came to the clinic was 7.3% ([4+5]/123). Conclusion: The relatively increased prevalence of SpA among patients who underwent LDH surgery indicates the necessity of increasing awareness on the new concept of axial SpA for specialists treating patients with low back pain.